Istikhdâm Uslûb al-Ta’allum li al-Mu’allim al-Nâtiq al-Aṣli bi al-Arabiyyah - Bashori, M.; Syaiful, Syaiful (Jurnal Alfazuna : Jurnal Pembelajaran Bahasa Arab dan Kebahasaaraban, 2023)
Purpose- Each teacher (lecturer) has a characteristic teaching style in the learning process. This study shows that the teaching style used by native Arabic speaking lecturers is a discussion-dialogue style. This can be aligned with the teaching style classification theory, namely the interactional teaching style. Design/Methodology/Approach- Researchers used a qualitative type method with a field approach. The aim is to describe directly in the field and then write about how to use the teaching style of native speaker lecturers and to review descriptively some of the student's opinions regarding the use of teaching styles and the impact they have on the process of learning Arabic. Then the data was collected and validated through three general instruments in qualitative research, namely observation, interviews and documentation. Findings- Apart from native speaker lecturers using a discussion-dialogue teaching style, native speaker lecturers combine teaching styles with other types of teaching styles to support success in the process of learning Arabic. Students are of the opinion that the teaching style of native Arabic speakers is not boring and has an impact on student enthusiasm and discipline in learning with native Arabic speakers. Research Limitation/ Implications- The limitations of the problem in this research focus on the use of the teaching style of native speaker lecturers at the KH Islamic boarding school Abdul Chalim Mojokerto.